Additive Effect on the Electrochemical Performance of Lithium–Sulfur Battery. (1st February 2015) - Azimi, Nasim; Xue, Zheng; Hu, Libo; Takoudis, Christos; Zhang, Shengshui; Zhang, Zhengcheng
Abstract: Lithium difluoro(oxalato) borate (LiDFOB) was investigated as an electrolyte additive for the Li-S battery. This additive was identified to be an efficient electrolyte additive to suppress the polysulfide shuttling effect existing in the conventional Li–S chemistry. To detect the positive impact of the new additive, oligo(ethylene glycol) functionalized silane was employed as the electrolyte solvent due to its high solvation capability with the lithium polysulfides. The electrochemical results and the SEM data of Li–S battery using the new electrolyte confirmed the role of the LiDFOB as a critical component to eliminate the shuttling of the dissolved polysulfides thus enabling a high coulombic efficiency.